Audit Strategi Mengungkap Dampak Status Uggp Terhadap Pengembangan Pariwisata Belitung - Ananda, Nuury Aulia; Huseini, Martani (JIAP (Jurnal Ilmu Administrasi Publik), 2024)
One of the tourism development concepts that is currently popular is geopark. There are 10 Indonesian National Geoparks that have received UNESCO Global Geopark (UGGp) status, one of which is the Belitung Geopark located in Belitung Regency, Bangka Belitung Province. However, this status was not a significant factor in policy formulation at the national level. This is because Belitung Regency Airport has been removed from the list of Indonesian International Airports. This UGGp status will be validated every 4 (four) years by assessors from UNESCO.  This revalidation activity will provide an assessment of the Geopark in several aspects, namely conservation, education and community empowerment. UNESCO uses a “card” system to evaluate and categorize UNESCO Global Geopark status. Geoparks that fail to meet UNESCO standards significantly risk losing their UNESO Global Geopark status if they fail to make comprehensive improvements within 2 (two) years. Therefore, it is very important to audit strategies in geopark development, especially in geoparks that already have UNESCO Global Geopark status, so that the status can be maintained to increase regional competitiveness, sustainable economic development and open opportunities for international cooperation